Transcriptome and metabolome profiling unveiled mechanisms of tea (Camellia sinensis) quality improvement by moderate drought on pre-harvest shoots. (December 2020) - Li, Meifeng; Liu, Jianjun; Zhou, Yuping; Zhou, Siqin; Zhang, Shuai; Tong, Huarong; Zhao, Aichun
Abstract: Conventional wisdom holds that tea ( Camellia sinensis ) quality can be improved by drought. To clarify the underlying mechanism, a conjoint analysis of transcriptome and metabolome profiling was carried out in tea shoots harvested under different soil water contents (SWCs). Drought had little impact on theanine, catechins and caffeine in field conditions. Besides the flavor contributions of amino acid and their derivatives, organic acids, and nucleotides and their derivatives, the obviously increased isoflavonoids and glycosylflavonoids and the sharply decreased lipids are suggested to play key roles, which is mainly due to substantial increases of type III polyketide synthase B ( PKSB ), flavonol synthase/flavanone 3-hydroxylase (FLS ), and UDP-glycosyltransferases ( UGTs ), as well as the significant repression of anthocyanidin synthase ( ANS ) and R2R3MYBs, and downregulated lipid metabolisms. Genes of GDSL esterase/lipase ( GDSL ), abscisic acid (ABA) and jasmonate (JA) signaling were found to play important roles in both flavonoid accumulation and lipid reduction. These findings increased our understanding of how moderate drought improves taste and aroma of tea by interfering in the metabolism of fresh leaves, which provides new insight into balancing compounds in pre-harvest tea shoots. Graphical abstract: Image 1 Highlights: Moderate drought improves tea flavor by balancing levels of specialised metabolites. Differentially accumulated flavonoids and lipids played a key role in tea flavor. PKSB, FLS, UGTs, ANS and R2R3MYBs played important roles in flavonoid accumulation. JA and ABA signaling were involved in the rebalance of the specialised metabolites.